Effects of profitable downsizing on collective bargaining - Sven Fischer; Werner Güth; Christoph Köhler (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We experimentally test how acceptance thresholds react to the decision of the proposer in a three party ultimatum game to exclude one of two responders with veto power from the game. We elicit responder acceptance thresholds in case the proposer decides to exclude one of them, what increases the available pie, and in case he doesnt exclude him despite strong monetary incentives. We find that on the aggregate level the proposers decision has no effect on acceptance thresholds. However, if the proposer excludes one responder, the distribution of thresholds becomes bimodal, indicating a polarization in behavior.
Keywords: C91; J52; 330; bargaining; experiment; labor markets; Personalabbau; Rentabilität; Lohnverhandlungen; Verhandlungstheorie; Gerechtigkeit; Emotion; Test